Labor and Product Market Reforms in Advanced Economies : Fiscal Costs, Gains, and Support - Banerji, Angana (Staff Discussion Notes; Staff Discussion Notes ;, 2017)
Product and labor market reforms are needed to lift persistently sluggish growth in advanced economies. But reforms have progressed slowly because of concerns about their distributive and short-term economic effects. Our analysis, based on new empirical and numerical analysis and country case-studies shows that most labor and product market reforms can improve public debt dynamics over the medium-term. This because reforms raise output by boosting employment and/or labor productivity. But the effect of some labor market reforms on budgetary outcomes and fiscal sustainability depends critically on business cycle conditions. Our evidence also suggests that some temporary and well-designed up-front fiscal stimulus can help enhance the economic impact of reforms. In the past, countries have used fiscal incentives in the past to facilitate reforms by alleviating transition and social costs. But strong ownership of reforms was crucial for their successful implementation.